Changes of Covey Affiliation by Bobwhite Quail in Tennessee - Noel S. Yoho; Ralph W. Dimmick (National Quail Symposium Proceedings, 2017)
This study was conducted on a 214-acre area of the Ames Plantation, Fayette County, Tennessee. Information on behavior of bobwhite quail (Colinus virginianus) during winter was obtained through flushing, trapping, color-marking, and telemetering quail during January-March, 1970. Interchange of quail between coveys was common; at least 20 incidences of change in covey affiliation were recorded. An average covey lost and gained a member every 3 days. Rapid replacement of birds lost from covey ranges was attributed to communication between coveys.